Physicochemical characteristics of liposome encapsulation of stingless bees' propolis - N. A., Ramli; N., Ali; S., Hamzah; N. I., Yatim (Elsevier Ltd, 2021)
Nutraceuticals from natural sources have shown potential new leads in functional food products. Despite a broad range of health-promoting effects, these compounds are easily oxidized and unstable, making their utilization as nutraceutical ingredients limited. In this study, the encapsulated stingless bees' propolis in liposome was prepared using soy phosphatidylcholine and cholesterol by thin-film hydration technique. Three different formulations of phosphatidylcholine composition and cholesterol prepared by weight ratio was conducted to extract high propolis encapsulation. Physicochemical changes in the result of the encapsulation process are briefly discussed using scanning electron microscopy and Fourier Transform Infrared Spectroscopy. A dynamic light-scattering instrument was used to measure the hydrodynamic diameter, polydispersity index, and zeta potential. The increment of the liposomal size was observed when the concentration of extract loaded increased. In comparing three formulations, F2 (8:1 w/w) presented the best formulation as it yielded small nanoparticles of 275.9 nm with high encapsulation efficiency (66.9%). F1 (6:1 w/w) formed large particles of liposomes with 422.8 nm, while F3 (10:1 w/w) showed low encapsulation efficiency with (by) 38.7%. The liposome encapsulation will provide an effective nanocarrier system to protect and deliver the flavonoids extracted from stingless bees' propolis.